Tax Avoidance in the Indonesian Energy Sector: The Role of Fraud and Governance - Andi Yaomil Diosana; Koenta Adji Koerniawan (Green Publisher Indonesia, 2025)
This study analyzes the relationship between profitability (ROA), transfer pricing (measured by the related-party receivables ratio), and financial statement fraud (assessed using the Beneish M-Score and Dechow F-Score) and the dependent variable, tax avoidance (CETR). Additionally, it examines the moderating role of the tax burden index. It adopts a descriptive quantitative design, utilizing secondary financial data from energy and mining companies listed on the Indonesia Stock Exchange over the period 2019 to 2023. Of all companies listed on the stock exchange, only 15 companies met the criteria of complete and consistent financial data during the observation period, yielding 75 firm-year observations. The results show that financial statement fraud significantly affects tax avoidance (β = -4.38e-14, p = 0.0030), while profitability (β = -1.247, p = 0.4835) and transfer pricing (β = 0.635, p = 0.3565) do not show significant effects. Furthermore, the tax burden index does not moderate the relationship between transfer pricing and tax avoidance (β = 4.386, p = 0.7947). These findings emphasize that behavioral factors, particularly profit manipulation, play a more dominant role than traditional financial indicators in driving tax avoidance. The implications of this study underscore the importance of strengthening corporate internal control mechanisms, improving financial reporting transparency, and ensuring tax compliance through effective regulation. The energy and mining sectors, which are at high risk of manipulative practices, require special attention so that tax avoidance practices can be minimized, fiscal justice supported, and the integrity of the overall taxation system strengthened.